PENGARUH FREKUENSI PEMBERIAN BIOFERTILIZER PSEUDOMONAD FLUORESEN TERHADAP PERTUMBUHAN TANAMAN PADI GOGO - Anhar, Azwir; Advinda, Linda; Handayani, Listi (Sainstek : Jurnal Sains dan Teknologi, 2012)
Pseudomonad fluorescents (Pf) is a biological agent that has been reported to enhance the growth of many plants because it can produce plant growth substance (auxin, gibberellins, and cytokinins), phosphate solvent enzyme, and siderofor. Information about the frequency of Pf in improving plant growth is limited. This study aimed to investigate the effect of  biofertilizer applied frequency on upland rice growth. The study was conducted from October to December 2011 in the screenhouse and Laboratory of Biological Department, Padang  State University. This study is experimental and the design used was randomized block design with 6 treatments and 5 replications. The treatment is the frequency of Pf applied there are without Pf (control), once, twice, three times, four times and five times. Data were analyzed using ANOVA and further test DNMRT the real level of 5%. The result showed that application of biofertilizer able to increasethe number of tillers and biomass of upland rice. However, the frequency of Pf has no effect on plant height, number of tillers, the wet weight and plant biomass.Key words : Pseudomonad flourescen, frequency, upland rice, biofertilizer